(untitled) (Archives of Mechanics - Test, 2004)
Coupled electro-elastic fields excited by a thermal inclusion in an isotropic dielectric medium with polarization gradient are studied in the framework of the Mindlin theory. An inclusion represents a plane heated layer differing from the outside medium only by its temperature. A series of problems are considered: an inclusion in an infinite medium, at a surface of a half-infinite body, in the middle or at the surface of a plate with free or clamped faces. The found Mindlin’s corrections to the fields of mechanical displacements, strains and stresses are expectably small. However, the arising accompanied electric fields localized in the narrow zones at surfaces and interfaces can have rather high amplitudes.